Cancer surgery during the Covid-19 pandemic in Turkey. (July 2020) - Alimoglu, Orhan; Erol, Cem Ilgin; Kilic, Furkan; Baysal, Hakan
Abstract: The coronavirus disease (Covid-19), which has spread rapidly all over the world after its appearance in December 2019, soon became a pandemic. In many places struck by the epidemic, clinical branches have prepared new guidelines for approaching the management of the disease in their area during the pandemic. Surgeons have also delayed elective surgeries. The first case of Covid-19 in Turkey was detected on March 10, 2020. After this date, 39 patients with a diagnosis of cancer were operated on in our clinic. In this study, we wanted to reveal the results of the cancer surgeries that we have performed during this period.